Jurnal Managemen Proyek Informatika Peran Penting Business Development Terhadap Perusahaan - Sofyan Mufti Prasetiyo; Ahmad Fauzi; Safira Madinah Widia; Yoggi Ilham Mulya (BULLET : Jurnal Multidisiplin Ilmu, 2022)
Business development is one of the most sought-after types of work by companies today. Companies need a business development for the continuity of the company itself so that it still exists, is relevant and profitable. Occupying a position as business development is how to help companies develop their business for the long term. BD is responsible for creating long-term corporate value through customers, markets and business relationships by creating opportunities for the company to continue to grow. With the increasing number of small businesses and startup companies in Indonesia, career opportunities as business development have also increased rapidly. This is because the company continues to compete with its competitors in order to stay ahead, both in terms of profits and brand awareness. one of the supporters of the process of establishing a long-term corporate valuation. This business development also plays a role as a creator of opportunities for the development of the company by way of optimizing the tasks of these components or factors.